Inovação organizacional e cultura organizacional na percepção de gestores de grandes empresas: estudo multicasos em empresas do setor de autopeças da região metropolitana de Sorocaba - Andrade, Luciana do Carmo Menezes de (2016)
With the crisis that has been going the automotive industry last year, it is necessary that companies in the auto parts sector go forward several changes to remain competitive. In this context, organizational innovation, which has the organizational culture as one of its main determinants, it is a key pillar of support competitiveness. Thus, this work is a multicases study in five large suppliers companies of auto parts of the metropolitan area of Sorocaba, aimed to analyze the practices of organizational innovation, and identify the factors related to the organizational culture of these companies are the key to the organizational innovation. As result, it was found that the adoption of organizational innovation practices is due to isomorphism in the automotive industries, but the organizational culture focused on innovation is essential for the occurrence of organizational innovation, and features such as financial (reward system, financial resources), organizational architecture (market orientation, mission, value and leadership), management tools (support innovation, teamwork, acceptance of risk and error tolerance, creativity, communication and management systems) are fundamentals. As factors that hinder organizational innovation were basically found problems related to people as: outgoing employees, lack of discipline, motivation, overwork, predesigned concepts, difficult to accept changes and unhappiness. The centralization of power, lack of autonomy and authoritarian leadership were also mentioned as inhibitors to the occurrence of organizational innovation.